Projetos de exploração florestal e restrições ao acesso e uso da Sociobiodiversidade pelas famílias da Comunidade Quilombola Flexinha, Municipio de Gurupá, Pará - GOMES, Neiva dos Santos (2023)
The transformations promoted by projects installed in the Amazon region have increased the demand for products from the region, wood extraction and, more recently, carbon sequestration. This article aims to analyze the influences of the forest exploration project on changes in agroextractive systems and sociobiodiversity in the Flexinha Quilombola Community, in the municipality of Gurupá, Pará. Interviews were carried out with key people and families in the community, participant observation, in addition to the use of the database obtained during the works of Tempo Comunidade of the Licentiate in Ethnodevelopment course. Forest exploration projects limited families in accessing and using socio-biodiversity because they degraded the forest, impacted agroextractive production, in addition to stirring up internal and external conflicts. The maintenance of local socio-biodiversity depends on the existence of policies that demonstrate the use of natural resources in a sustainable way, and not on an economic model that will alter local agroextractive systems, leaving traces of destruction and conflicts and that privileges some social groups, while destroying the possibilities of life to others.